SOUTH AFRICAN NAVAL PERSONNEL SECONDED TO THE ROYAL NAVY 1940-1942 - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Statistics of South African naval personnel seconded to the Royal Navy between December 1943 and September 1945 have been published in Annexure B to an article in Militaria 12/11982. Since then I have traced similar statistics in the SADF Archives for June 1940 and June 1941. To these I have added details extracted from the Navy Listsfor August 1941 and August 1942.